THE QUALITY OF INFORMATION SYSTEM SERVICES AND INTEGRATED VILLAGE ADMINISTRATION SERVICES IN THE IMPLEMENTATION OF CERTIFICATES BY THE VILLAGE GOVERNMENT IN SELAMANIK VILLAGE, CIPAKU DISTRICT, CIAMIS DISTRICT - Atika Lasmanah; Arie Budiawan; Otong Husni Taufiq (Faculty of Social and Political Science Universitas Galuh, 2020)
This research is motivated by the inadequate information system services and integrated village administration services in the making of a letter of incapacity by the village government in Selamanik Village, Cipaku District, Ciamis Regency. This is due to the lack of quality of services provided by the Village government in making the Certificate of Disability (SKTM), the slow processing of a service, the lack of socialization from the Village government regarding the procedure for making a Certificate of Disability (SKTM). The purpose of this study was to determine the Quality of Information System Services and Integrated Village Administration Services in the Making of a Certificate of Inability by the Village Government in Selamanik Village, Cipaku District, Ciamis Regency. The research method used in this study is qualitative in a descriptive approach. The formulation of the problem in this study is as follows, How is the quality of information system services and integrated village administration services in making a certificate of incapacity by the village government in Selamanik village, Cipaku district Ciamis ?, What are the obstacles to the Integrated Village Administration Service and Information System services in the Making of a Certificate of Inability by the Village Government in Dea Selamanik, Cipaku District, Ciamis Regency ?, What are the efforts made to the Information System and Integrated Village Administration Service in Making a Letter of Inability by the Village Government in Selamanik Village, Cipaku District, Ciamis Regency? The results of the research show that the services provided are still not optimal, this is because the provision of services is still not following community expectations. The obstacles faced by the village are not providing services following the minimum service standards, not being fully friendly to the community, the procedures that must be followed in service, are still complicated. The suggestions that can be given to village governments are that services provided to the community must be given to the maximum, following community expectations. Quality service if people feel satisfied.